Cost Volume Profit (CVP) Analysis in Determining the Number of Units to Achieve Profit Targets (Case Study on Byta Hijab) - Agustin Pratiwi; Filsa Soraya; Ayrofal Anam; Mochamad Reza Adiyanto (Formosa Journal of Applied Sciences, 2023)
This research aims to determine the profit target achieved using Cost Volume Profit (CVP) at Byta Hijab. This research uses a case study approach and research data was obtained through interviews with the owner of Byta Hijab. This research used qualitative descriptive research with a case study approach. The data collection techniques in this research are observation by visiting for 1 day, interviews with business owners and documentation by searching for data in the form of financial data and photographs as a complement to primary data. The data analysis technique used is Cost Volume Profit (CVP) analysis by determining the number of units that must be sold to achieve the business profit target. The research results show that the CVP method produces more accurate profit target calculations than traditional methods